2015
DOI: 10.17577/ijertv4is040743
|View full text |Cite
|
Sign up to set email alerts
|

Buckling Analysis of Composite Cylinders Subjected to Axial Compressive Loads

Abstract: Slender structures will buckle when subjected to pressure or compressive loads. Buckling is also important factor to decide the failure of the structure. Generally columns and higher length cylinders will buckle and they will be manufactured by the metals. In the present work slender cylinder subjected to axial compressive load manufactured by different composite materials is analyzed. The effect of cylinder length to thickness ratio, materials and stacking angle are analyzed. It results that as the cylinder l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…An initial geometric imperfection has been widely reported to be a single dominant factor, which contributed to the discrepancy between theories and experiments [9][10][11][12][13]. Kumar et al [14] predicted Nonlinear-buckling analysis as a better method and suggested it for calculation or estimation of actual structures. Peining et al [15] points out that stiffness eccentricity is a major factor that causes axial buckling than the combined load.…”
Section: Introductionmentioning
confidence: 99%
“…An initial geometric imperfection has been widely reported to be a single dominant factor, which contributed to the discrepancy between theories and experiments [9][10][11][12][13]. Kumar et al [14] predicted Nonlinear-buckling analysis as a better method and suggested it for calculation or estimation of actual structures. Peining et al [15] points out that stiffness eccentricity is a major factor that causes axial buckling than the combined load.…”
Section: Introductionmentioning
confidence: 99%